Bloqueio infiltrativo de lidocaína em variohisterectomia convencional ou videoassistida em cadelas - Bäumer, Sabrina (2015)
The objective of this study was to evaluate how efficient preoperative infiltration of lidocaine hydrochloride for postoperative pain control of female dogs subjected to conventional or video assisted ovariohysterectomy. Twenty eight healthy dogs were selected, having been medicated with acepromazine maleate (0.05 mg kg-1) induced to propofol anesthesia (4 mg kg-1) and kept under inhalational general anesthesia with vaporized isoflurane in oxygen at 100% in a partial gas re-inhalation system. All the animals received transoperatory analgesia through the administration of fentanyl in continued infusion (20 μg kg hr -1) after a bolus dose (2.5 μg kg -1). The animals were randomly allocated into two large groups: CG (control group; with an infiltration of saline solution into the surgical incision line or portal entrance site, n=14) and BG (block group; following the same method, however with a 2% lidocaine infiltration, n=14, with a dose of 4mg kg-1). Each group was subdivided into two more groups, according to the surgical procedure to be submitted to: CCG (celiotomy control group, n=7), VCG (video control group, n=7), CBG (celiotomy block group, n=7) and VBG (video assisted block group, n=7). In the immediate post-anesthetic period, a commercial association of metamizole and n-butylscopolamine 25mg kg-1, was administered, being repeated every eight hours for 48 hours. For the evaluation of postoperative pain the instruments used were the visual analogue scales (VAS), from the University of Melbourne and the simplified one from Glasgow, at the same time as the measurement of glycemia and seric cortisol. The data was submitted to the Shapiro-Wilk normality test at a level of 5% significance. The normality of the residue was not observed, the non-parametric Kruskal-Wallis test for within the groups in different moments. Afterward, the Tukey and the Dunn tests were applied for pair comparison, at a level of 5% significance. One animal suffered rescue analgesia in the CBG, one in the VCG, seven in CCG and three in the VBG, before the proposed total evaluation times. There was a difference at one and two hours (p<0.001) of postoperative for the CCG in relation to the others, one hour into the postoperative for the VCG (T1) also presented a rise in pain levels in relation to the CBG and VBG, in relation to the pain scales evaluated. For the glucose there was a rise for CCG at T1. However, for the cortisol evaluation, there was a rise at T1 for CCG in relation to the others and VCG and CBG in relation to VBG. Still at T6 there was a rise in cortisol to CBG in relation to the others. The analysis of the results allows to conclude that the infiltrative block of lidocaine together with the association of metamizole and n-butylscopolamine IV in immediate postoperative constitutes an adequate analgesic protocol for conventional and video-assisted OVH, and plus, that the latter gives a smaller algic stimulus than the conventional one.